Using Drawing and Sketch to Teach Speaking Ability for Young Learners: Penelitian - Puput Jianggimahastu; Rida Fahas (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Teaching and learning English is not easy, especially for young students. In recent years, teachers have been focusing on innovative approaches to improve language comprehension, including drawing and sketching techniques that have proven successful, especially in improving speaking skills. These methods capitalise on children's visual and creative abilities, resulting in a dynamic language learning platform that involves both cognitive and artistic skills. This study investigated ten students in grade four at SD Negeri Klitik. They showed significant improvement in their English speaking ability when they used visual aids such as pictures related to their work and interactive activities such as drawing and sketching game boards. As a result, students had a better ability to convey their ideas, a wider vocabulary, and greater confidence in communicating verbally. Lev Vygotsky and Howard Gardner's theories on education and developmental psychology are in line with this approach. These theories emphasise the importance of using multiple sensory channels during the learning process. Therefore, incorporating drawing and sketching activities in language education can make language learning more interesting, fun and effective for children.